“Fierce and Free, or Caged and Cowed”: Interspecies Oppression and Survival in Lucy Ellmann’s Ducks, Newburyport - Elisa Pesce (European Journal of American Studies)
Lucy Ellmann’s Ducks, Newburyport (2019) explores the social, cultural, and environmental crises of the contemporary United States from the perspective of a white, middle-aged woman and mother of four. Her angst-ridden interior monologue is interrupted only by short sections of third-person prose that relate the story of a mountain lioness in search of her lost cubs. While the juxtaposition of these two narrative strands serves Ellmann’s explicit purpose of drawing a parallel between experiences of motherhood and denouncing the way capitalist and patriarchal societies have historically rested on the oppression of both women and nature, this paper argues that Ducks, Newburyport also advocates for a renewed commitment to harmonious interspecies coexistence through the story of the protagonist’s eldest daughter, Stacy. A moody and troubled teenager, Stacy single-handedly saves her family from a gun attack, following which the narrator thinks that her daughter’s courage was inspired by “some kind of rapport” (Ellmann 998) that she feels with the recently captured lioness. In light of the wild creature’s function of foil for both the narrator and Stacy (De Bruyn 274-79), I propose that Ellmann presents interspecies articulations as a harbinger of hope in a cultural context in which the girl is nevertheless constantly forced to navigate the tensions between the aspects of her connection to the animal world that make her fierce and free and those that work to keep her—and symbolically all women, minority groups, and nature—caged and cowed.